Divergent acute versus prolonged pharmacological GLP-1R responses in adult β cell-specific β-arrestin 2 knockout mice - Bitsi, Stavroula (2023)
The glucagon-like peptide-1 receptor (GLP-1R) is a major type 2 diabetes therapeutic target. Stimulated GLP-1Rs are rapidly desensitized by β-arrestins, scaffolding proteins that not only terminate G protein interactions but also act as independent signaling mediators. Here, we have assessed in vivo glycemic responses to the pharmacological GLP-1R agonist exendin-4 in adult β cell-specific β-arrestin 2 knockout (KO) mice. KOs displayed a sex-dimorphic phenotype consisting of weaker acute responses that improved 6 hours after agonist injection. Similar effects were observed for semaglutide and tirzepatide but not with biased agonist exendin-phe1. Acute cyclic adenosine 5'-monophosphate increases were impaired, but desensitization reduced in KO islets. The former defect was attributed to enhanced β-arrestin 1 and phosphodiesterase 4 activities, while reduced desensitization co-occurred with impaired GLP-1R recycling and lysosomal targeting, increased trans-Golgi network signaling, and reduced GLP-1R ubiquitination. This study has unveiled fundamental aspects of GLP-1R response regulation with direct application to the rational design of GLP-1R-targeting therapeutics.